TRAINING ON THE USE OF CAPCUT APPLICATION AS DIGITAL-BASED LEARNING MEDIA AT SMPN 4 TAMBANG - Nurjanis, Nurjanis; Hadi, Firdaus El; Nugraha, Yudhi Martha (Universitas Pahlawan Tuanku Tambusai, 2024)
This article is the result of dedication that aims to explain the use of the capcut application as one of the effective digital-based learning media implemented at SMPN 4 Tambang Kampar Regency. This service activity is to introduce information literacy to students by identifying various sources of information based on their quality and credibility, technical skills to seek information as well as knowledge and techniques to avoid plagiarism and other unethical actions. One of the digital-based media is capcut which is an application for editing videos that previously had the name viamaker. Capcut has now become a favorite application that offers a variety of free features, including a variety of effects, so that the resulting content is better and more interesting. This devotion is by conducting several activities with a lecture, discussion and practice approach. Previously, teachers did not recognize the application as one of the learning media. However, after socialization, teachers then become more familiar with the application and are literate about the development of learning so that during teaching in class it appears more attractive and teachers are also able to develop themselves so as not to be left behind with the development of technology and information.